The Concept and Essence of Economic Conflict - BOLSHAKOV, Andrey; TERESHINA, Yelena; KHRAMOVA, Yevgeniya; MAVRIN, Oleg; MANSUROV, Timur (Journal of Advanced Research in Law and Economics; Vol 7 No 8 (2016): JARLE Volume VII, Issue 8(22), Winter 2016, 2017)
The article treats the economic conflict as a concept and socio-economic phenomenon, reveals the main methodological approaches to the study of conflict in the economic sphere. Using analyzed approaches the authors emphasize key features that characterize the essence of economic conflict.